2023
DOI: 10.3390/jcm12062105
|View full text |Cite
|
Sign up to set email alerts
|

Bone Cement and Its Anesthetic Complications: A Narrative Review

Abstract: The concept of bone cement implantation syndrome (BCIS) is not yet fully understood. In patients undergoing cemented hip arthroplasty, it is a significant factor in intraoperative mortality and morbidity. It may also manifest in a milder form postoperatively, resulting in hypoxia and confusion. In the older population, hip replacement surgery is becoming more prevalent. The risks of elderly patients suffering BCIS may be increased due to co-existing conditions. In this article, we present a narrative review of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 66 publications
0
20
0
Order By: Relevance
“…PMMA, sometimes referred to as MMA or bone cement , was first used in orthopedic surgery in 1965 and later received approval from the U.S. Food and Drug Administration (FDA) in 1970 [ 1 ]. In 1970, Powell et al.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…PMMA, sometimes referred to as MMA or bone cement , was first used in orthopedic surgery in 1965 and later received approval from the U.S. Food and Drug Administration (FDA) in 1970 [ 1 ]. In 1970, Powell et al.…”
Section: Discussionmentioning
confidence: 99%
“…This mechanism proposes that when activated for use in orthopedic surgery, MMA results in a very strong exothermic reaction that results in the rapid expansion of the bone cement within the desired bone cavity in which it is placed. It has been postulated that MMA has very strong direct cardiopulmonary depressant effects and is rapidly absorbed into the bloodstream via the bone marrow, resulting in a rapid and noxious bolus to the heart and lungs once placed in the patient [ 1 ]. In vitro studies demonstrated direct vasodilatory effects of MMA; however, in vivo animal studies failed to demonstrate sufficient plasma concentration of MMA following cemented hip arthroplasty to achieve the significant cardiopulmonary effects commonly seen in BCIS [ 1 , 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bone cement was originally named "materials based on polymethyl methacrylate" and are currently used in clinical practice [8]. Nevertheless, these materials have several disadvan-tages, such as an exothermic setting reaction (which can lead to damage to adjacent tissues) and the need for revision surgery [9].…”
Section: Introductionmentioning
confidence: 99%